2015
DOI: 10.3390/md13031224
|View full text |Cite
|
Sign up to set email alerts
|

Potential Threats Posed by New or Emerging Marine Biotoxins in UK Waters and Examination of Detection Methodology Used in Their Control: Brevetoxins

Abstract: Regular occurrence of brevetoxin-producing toxic phytoplankton in commercial shellfishery areas poses a significant risk to shellfish consumer health. Brevetoxins and their causative toxic phytoplankton are more limited in their global distribution than most marine toxins impacting commercial shellfisheries. On the other hand, trends in climate change could conceivably lead to increased risk posed by these toxins in UK waters. A request was made by UK food safety authorities to examine these toxins more closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 100 publications
0
22
0
1
Order By: Relevance
“…This might be unknown YTX analogues, or possibly another type of lipophilic toxin. Brevetoxins (BTxs) and palytoxins (PlTxs) are known to be extracted with methanol (Reverte et al 2014;Turner et al 2015). However, to detect BTxs, the addition of ouabain and veratridine (O/V) during exposure of the cells is needed.…”
Section: Shellfish Samples Contaminated With Lipophilic Marine Biotoxinsmentioning
confidence: 99%
“…This might be unknown YTX analogues, or possibly another type of lipophilic toxin. Brevetoxins (BTxs) and palytoxins (PlTxs) are known to be extracted with methanol (Reverte et al 2014;Turner et al 2015). However, to detect BTxs, the addition of ouabain and veratridine (O/V) during exposure of the cells is needed.…”
Section: Shellfish Samples Contaminated With Lipophilic Marine Biotoxinsmentioning
confidence: 99%
“…Microalgae can produce a broader spectrum of toxic compounds than illustrated in Table 2 and include yessotoxins (YTXs) and pectenotoxins (PTXs) that mainly cause diarrhoea (Reguera et al 2014). An increasing number of toxic compounds derived from algae are being detected as monitoring and analytical tools become more advanced, including brevetoxins (Turner et al 2015) and cyclic imines (Davidson et al 2015).…”
Section: Global Distribution and Characterisation Of Habs Affecting Hmentioning
confidence: 99%
“…The absence of external indications, limited techniques of determination as well as thermostability of CTXs and BTXs have become concomitant factors causing local CFP and NSP outbreaks in countries that are located distant from the common habitats of these algae [ 40 ]. Tens of ciguatera cases caused by consummation of contaminated fish were already recorded in various countries of Europe and America [ 16 , 43 ]. It has to be taken into account that the area of the occurrence of ciguatera fishes may be wider than the harmful algae habitat itself because of the possibility of long distance migration of contaminated fish.…”
Section: New Data On the Geographic Distribution Of Gambmentioning
confidence: 99%
“…Firstly, the global warming has contributed to the emergence of dinoflagellate species in previously subtropical and even temperate regions [ 16 ]. Secondly, it has been found that this temperature range itself may be wider than thought [ 43 ]. Finally, the anthropogenic factor plays an important role in the distribution of these microalgae.…”
Section: New Data On the Geographic Distribution Of Gambmentioning
confidence: 99%
See 1 more Smart Citation